Restrukturisasi Organisasi dan Kualitas Pelayanan di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kota Makassar - Darwis Darwis; Mohamad Thahir Haning; Nur Indrayati Nur Indar (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
This study aims to determine the Organizational Restructuring and Service Quality in the One-Stop Integrated Service Investment Service in Makassar City. The type of research in this research is quantitative with a descriptive style. The population in this study are all people who take care of permits at DPMPTSP Makassar City. The sample in this study amounted to 75 people. The data collecting technique in this research is using a questionnaire. Then the collected data were analyzed descriptively quantitatively. This study's results indicate that the variable of organizational restructuring includes the complexity of 62.3, formalization of 62.2, and centralization of 61.9. Meanwhile, service quality variables include reliability 61.26, tangible 66.13, responsiveness 62.26, Assurance 58.53, and empathy 62.4.